(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Crimes committed on or utilizing the Internet media are known as cyber-crimes. These include an abundance of illicit activity. The word cyber-crime is an umbrella term for the grouping of various unlawful actions. The anonymous nature of the internet allows offenders to engage in many kinds of illegal acts termed cyber-crimes due to numerous unpleasant behaviors taking place in the cyber-space and the study which discussed about, cyber crime, Cyber-crime perpetrators, Cyber crime in the world, Different types of cyber-crimes, Cyber crime and cyber law, Common cyber crimes, Nature of cyber-crime acts, Application of the cyber crimes theory, Cyber law in India.